2014
DOI: 10.1523/jneurosci.3129-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancement or Cognitive Cost: Trait-Specific Outcomes of Brain Stimulation in the Case of Mathematics Anxiety

Abstract: The surge in noninvasive brain stimulation studies investigating cognitive enhancement has neglected the effect of interindividual differences, such as traits, on stimulation outcomes. Using the case of mathematics anxiety in a sample of healthy human participants in a placebo-controlled, double-blind, crossover experiment, we show that identical transcranial direct current stimulation (tDCS) exerts opposite behavioral and physiological effects depending on individual trait levels. Mathematics anxiety is the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
161
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(173 citation statements)
references
References 37 publications
10
161
1
1
Order By: Relevance
“…One cannot meaningfully speak of enhancement when a substantial portion of individuals shows no response or even a detriment. Potential costs to cognitive enhancement are often overlooked, but are a real possibility: enhancement of one cognitive function could be paired with a decline in another function (Brem et al 2014a;Iuculano and Cohen Kadosh 2013;Sarkar et al 2014), as the brain networks underlying cognitive functions do not operate in isolation (Wokke et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One cannot meaningfully speak of enhancement when a substantial portion of individuals shows no response or even a detriment. Potential costs to cognitive enhancement are often overlooked, but are a real possibility: enhancement of one cognitive function could be paired with a decline in another function (Brem et al 2014a;Iuculano and Cohen Kadosh 2013;Sarkar et al 2014), as the brain networks underlying cognitive functions do not operate in isolation (Wokke et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of arithmetic, several studies have investigated the beneficial effect of tDCS on various aspects of arithmetic problem solving and learning [13,16,17,36]. However, despite first progress, the findings thus far are relatively heterogeneous and different stimulation protocols being beneficial only for a narrow set of cognitive processes and skills.…”
Section: Discussionmentioning
confidence: 99%
“…In the arithmetic domain, first studies have demonstrated that tDCS can affect arithmetic performance and learning [13][14][15][16]. However, the observed effects strongly depended on the cognitive processes involved in the arithmetic operation as well as the placement of the tDCS electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that, depending on the stimulated brain regions, anodal tDCS influences arousal during emotion regulation [20], regulation of negative emotions in situations characterized by social exclusion [63,64], mathematics anxiety [67], emotional reactions to pain stimuli [62], negative affect for negative pictures [59], negative affect for negative stimuli [56], and momentary ruminative self-referent thoughts [76].…”
Section: Emotion Regulation Rtmsmentioning
confidence: 94%
“…In a study on mathematics anxiety in healthy subjects using tDCS and salivary cortisol, Sarkar et al [67] expected that anodal stimulation to the left DLPFC and inhibitory cathodal stimulation to the right DLPFC would produce the greatest reduction in negative emotional reactions. The authors based this on previous studies related to salivary cortisol [8] and positive and negative emotional processing of the left and right DLPFC ( [31,78].…”
Section: Emotion Regulation Rtmsmentioning
confidence: 99%